Distance Learning and Student Anxiety at Palangkaraya University - Perdana Indra; Sasmithae Lia (AL-ISHLAH: Jurnal Pendidikan, 2021)
The Covid-19 pandemic has had a profound effect on the entire world, including the field of education. Students at the Faculty of Medicine experience anxiety due to distance learning. The purpose of this study was to ascertain the extent to which distance learning affects the anxiety level of students at the Faculty of Medicine, University of Palangkaraya. The research was conducted using a descriptive quantitative design. The population for this study was comprised of all students at the University of Palangkaraya's Faculty of Medicine and 219 individuals. The modified Halmilton Anxiety Rating Scale was used as the research instrument (HARS). The findings indicated that the greatest challenge encountered during distance learning was the absence of direct practical work (39 %). According to the level of anxiety, 141 respondents (64.38%) reported experiencing no symptoms of anxiety, 48 respondents (21.91%) reported experiencing mild anxiety, 22 respondents (10.04 %) reported experiencing moderate anxiety symptoms, and eight respondents (3.67%) reported experiencing severe anxiety. When anxiety symptoms manifest, the behavioral response manifests the highest percentage of mild anxiety symptoms, at 43.83%; the cognitive response manifests at 29.22 %; and the physiological and affective responses manifest at the same rate, at 26.48 %. The moderate and severe anxiety levels indicated that cognitive responses accounted for the highest anxiety response, at 18.27 % and 8.19 %, respectively. The study's conclusion indicates that distance education has a variable effect on the emergence of anxiety in medical faculty students at the University of Palangka Raya. As a result, support from various stakeholders is required to pay attention to the impact of distance learning on students.